Pengaruh Penerapan Model Pembelajaran Inkuiri Terbimbing pada Materi Ciri-Ciri Makhluk Hidup Kelas VII di SMP Negeri 7 Kota Bengkulu - Anggraini, Elistin (Yayasan Darussalam Bengkulu, 2024)
The guided inquiry learning model is a learning approach that can increase student participation and learning achievement. In this model, teachers and students work together to formulate problems, and students actively seek answers and conclude their own learning results. This research aims to evaluate Biology Science learning outcomes regarding the Characteristics of Living Creatures material for class VII students at SMPN 7 Bengkulu City and to assess the positive influence of implementing the Guided Inquiry Learning Model on these learning outcomes. The research method used is quantitative with a Quasi Experimental Design research design and a non-equivalent control group design. Data is collected through written tests, image documentation, photos and grades related to learning outcomes. Data analysis used the t test, and the results showed a tcount value of 5.764 > ttable 1.994. These results indicate that the Guided Inquiry Learning Model has a significant influence on student learning outcomes in Class VII Characteristics of Living Creatures at SMPN 7 Bengkulu City. The magnitude of the influence of this learning model is categorized as moderate, with an impact value (d) of 0.78.